2011
DOI: 10.1007/s00405-011-1665-0
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the knowledge of nasopharyngeal carcinoma among medical doctors at primary health care level in Perak state, Malaysia

Abstract: Nasopharyngeal carcinoma (NPC) is among the commonest cancers in Malaysia. The prognosis for NPC like most other head and neck cancer is dependent on its staging. Majority of patients in Malaysia at the time of diagnosis are either at stage III or IV (27 and 47%, respectively). The lack of knowledge among primary care medical doctors regarding NPC may contribute to this delay in diagnosis. The aim of this study was to assess the knowledge of the primary care doctors in the state of Perak on the various aspects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…There is a low rate of lymph dissemination, it does not exceed 15% in the various series reported [ [3] , [4] , [5] , [6] , [7] ]. The incidence rate of distant metastases is comparable to the other nasopharyngeal tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a low rate of lymph dissemination, it does not exceed 15% in the various series reported [ [3] , [4] , [5] , [6] , [7] ]. The incidence rate of distant metastases is comparable to the other nasopharyngeal tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The most common symptoms are usually epistaxis, nasal blockage, and masses in the neck, that appear much earlier in patients with NPC, due to earlier diagnosis [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…They also found that when medical doctors in Malaysia were asked if they thought they had enough knowledge to diagnose NPC, 88.7% of the participants answered no. 25 Prasad and Pua noticed a ‘doctors-delay’ of 127 days before diagnosis, acknowledging that there is a need to create more awareness among first-line doctors. However, it is not just the GP in the PHCC who plays an important role in the late presentation at diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Literature suggests that insufficient awareness of NPC amongst health professionals contributes to delayed recognition.10 According to studies conducted in Indonesia and Malaysia, GPs in these regions lack the requisite knowledge to diagnose and refer patients with suspected NPC [16,17].…”
Section: Introductionmentioning
confidence: 99%